2011
DOI: 10.1007/978-3-642-22993-0_33
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Finite Automata and Probabilistic Reversible Automata: R-trivial Idempotent Languages

Abstract: We study the recognition of R-trivial idempotent (R1) languages by various models of "decide-and-halt" quantum finite automata (QFA) and probabilistic reversible automata (DH-PRA). We introduce bistochastic QFA (MM-BQFA), a model which generalizes both Nayak's enhanced QFA and DH-PRA. We apply tools from algebraic automata theory and systems of linear inequalities to give a complete characterization of R1 languages recognized by all these models. We also find that "forbidden constructions" known so far do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Freivalds with his students visited me at Berkeley, Princeton and Waterloo. He was particularly fascinated by the result that the power of QFAs changed with the success probability and its parallels with his work on FIN and spent a lot of time with his students figuring out when and how exactly the power of QFAs changed, with me also contributing some ideas to this work (Ambainis et al, 1999, Ambainis et al, 2001, Ambainis and Kikusts 2003, Golovkins et al 2011.…”
Section: Our First Quantum Collaborationmentioning
confidence: 99%
“…Freivalds with his students visited me at Berkeley, Princeton and Waterloo. He was particularly fascinated by the result that the power of QFAs changed with the success probability and its parallels with his work on FIN and spent a lot of time with his students figuring out when and how exactly the power of QFAs changed, with me also contributing some ideas to this work (Ambainis et al, 1999, Ambainis et al, 2001, Ambainis and Kikusts 2003, Golovkins et al 2011.…”
Section: Our First Quantum Collaborationmentioning
confidence: 99%
“…The transformations T σ 's of NaQFA as for LaQFA, the acceptance rule R is as for KWQFA. Bistochastic quantum finite automaton (BiQFA) [49] is a generalization of NaQFA such that the transformations T σ 's can be bistochastic quantum operations and the acceptance rule R is as for KWQFA.…”
Section: One-way Qfasmentioning
confidence: 99%
“…While 1KWQFAs recognize more languages than MCQFAs and LaQFAs, they cannot recognize some regular languages [62], for example, {{a, b} * a} / ∈ BMM. Researchers [7,30,49] have also shown that if a minimal 1DFA has some certain properties, called forbidden constructions, then its language cannot be recognized by KWQFAs for any or for some error bounds. Using forbidden constructions, it was also shown that BMM is not closed under intersection or union [8].…”
Section: Bounded-error Language Recognition In Restricted Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…4. The details of a random walk on the input w generalizations of this QFA model, e.g., [18,3,12]. In Section 4.5, we saw a twoway QFA model that has classical as well as quantum states, and the classical states govern the computation flow and the determination of whether intermediate measurements or unitary transformations should be performed, depending on both input symbols and previous measurement results.…”
Section: General Qfasmentioning
confidence: 99%